Study Protocol of a Distance Learning Intervention to Support Social Emotional Learning and Identity Development for Adolescents Using Interactive Mobile Technology - Megan Cherewick; Sarah Lebu; Christine Su; Lisa Richards; Prosper F. Njau; Ronald E. Dahl (Frontiers Media S.A., 2021)
Background: The maturational period from age 10 to 14-often referred to as very young adolescents (VYAs)-represents a dynamic period of learning and neurobehavioral development as individuals transition from childhood to adolescence. This developmental period presents a window of opportunity for strategic investment to improve trajectories of health, education and well-being among young people. More specifically, neurodevelopmental changes during pubertal maturation influence neural circuitry involved in processing emotions, risks, rewards and social relationships. Technology can be leveraged to create social emotional learning experiences for VYAs and provide opportunities for flexible, distance learning in low-income countries. The aim of this study protocol is to detail how insights from developmental science can be used to inform the intervention design, implementation and evaluation of a distance learning, social emotional learning intervention for VYAs.Methods: This study will be delivered to 500 VYAs in Temeke District, Dar es salaam. Study participants will watch culturally-relevant, animated videos on social emotional mindsets and skills and content will be paired with experiential learning activities over a period of 10 weeks. A nested smart-phone based study will practice learning social emotional skills and mindsets through engagement with multi-media material via the WhatsApp messenger application. Surveys and in-depth interviews will be administered to adolescents, their parents/caregivers and teachers before and after the intervention to evaluate the effect of the intervention on study outcomes.Discussion: This study is among the first to provide results on how to effectively design a distance-learning intervention to promote social emotional learning and identity development within a low-resource context. The findings will provide substantial evidence to inform new intervention approaches that are effective in low-resource contexts and strategies to reach scale among similar programs invested in leveraging technology to support adolescent health and development.Clinical Trial registration: Study registered with ClinicalTrials.gov. Identifier number NCT0445807.